Antioxidant activity of methanolic extract from yellow paprika (Capsicum annuum, L.) by DPPH radical scavenging method - Warsi, Warsi; Guntarti, Any (Pharmaciana, 2017)
Yellow paprika (Capsicum annuumL.) is one of fruit that contains of carotenoid compounds as an antioxidant. This reasearch was aimed to know an antioxidant capacity of methanolic extract from yellow paprika with 2,2âdiphenylâ1âpicrylhydrazyl (DPPH) radical scavenging method. The fresh yellow paprika was determined of its loss of drying by gravimetric. The yellow paprika extract was obtained by maceration using methanol as solvent. The content of Î²âcarotene from this extract was analyzed qualitively by thin layer chromatography and UV-Vis spectrophotometer. The antioxidant activity of methanolic extract from yellow paprika was determined base on measurement of residual DPPH by UVâVis spectrophothometric at wavelength of 515.6 nm. The data was used to calculate % inhibition. Furthermore, IC50 value was determined to know potency of its antioxidant. The result of loss of drying yellow paprika fruit was obtained 6.33 Â± 0.02 %. The analysis with thin layer chromatography and UV-Vis spectrophotometer showed that this fruit was contain of Î²âcarotene. The result of antioxidant activity analysis from yellow paprika fruit was obtained IC50 value of 0.3028 Â± 0.0093 mg/mL. The result of the research showed that the antioxidant potency of yellow paprika was less than Î²âcarotene (IC50 0.0852 Â± 0.0009 mg/mL).